Observation of magnetic anomalies in one-step solvothermally synthesized nickel-cobalt ferrite nanoparticles - Datt, Gopal; Sen Bishwas, Mousumi; Raja, M. Manivel; Abhyankar, A. C. (Nanoscale, 2016)
Magnetic anomalies corresponding to the Verwey transition and reorientation of anisotropic vacancies are observed at 151 K and 306 K, respectively, in NiCoFe2O4 nanoparticles (NPs) synthesized by a modified-solvothermal method followed by annealing. Cationic disorder and spherical shape induced non-stoichiometry suppress the Verwey transition in the as-synthesized NPs. On the other hand, reorientation of anisotropic vacancies is quite robust. XRD and electron microscopy investigations confirm a single phase spinel structure and the surface morphology of the as-synthesized NPs changes from spherical to octahedral upon annealing. Rietveld analysis reveals that the Ni2+ ions migrate from tetrahedral (A) to octahedral (B) sites upon annealing. The Mossbauer results show canted spins in both the NPs and the strength of superexchange is stronger in Co-O-Fe than Ni-O-Fe. Magnetic force images show that the as-synthesised NPs are single-domain whereas the annealed NPs are multi-domain octahedral particles. The FMR study reveals that both the NPs have a broad FMR line-width; and resonance properties are consistent with the random anisotropy model. The broad inhomogeneous FMR line-width, observation of the Verwey transition, tuning of the magnetic domain structure as well as the magnetic properties suggest that the NiCoFe2O4 ferrite NPs may be promising for future generation spintronics, magneto-electronics, and ultra-high-density recording media as well as for radar absorbing applications.